Disposition kinetics of tylosin administered intravenously and intramuscularly in Desert Sheep and Nubian Goats - Taha, A.A.; Elsheikh, H.A.; Khalafalla, A.E.; Osman, I. A. M.; Abdullah, A. Salam (Elsevier, 1999)
The pharmacokinetic behaviour of tylosin was compared in five Desert sheep and five Nubian goats. The animals were given a single dose of 20% tylosin (15 mg/kg), either intravenously (i.v.) or intramuscularly (i.m.). Following i.v. administration, the volumes of distribution and the elimination half-life times were similar in both species, whereas in goats a greater volume of the central compartment and faster clearance were observed. For the i.m. route, similar pharmacokinetics were observed in both species. The bioavailability (f) of the drug in goats (0.84 ± 0.11) was not significantly higher than that in sheep (0.73 ± 0.08). The present study has shown that, despite the significant differences in some of the drug pharmacokinetic parameters between sheep and goats for the i.v. route, identical intravenous and intramuscular dosage regimens of tylosin may be recommended for the two species.